PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SO GOOD FOOD MANUFACTURING KABUPATEN TANGERANG TAHUN 2020 - Muhamad Riziq Shihab; Wawan Prahiawan; Vera Maria (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the effect of work discipline, work motivation and work environment on employee performance. The research population is all employees of PT. So Good Food Manufacturing Tangerang Regency as many as 914 employees. The research sample was 120 employees who were determined based on the hair formula with probability sampling technique. Data analysis techniques used: Descriptive Statistics, Data Quality Test, Classical Assumption Test, Multiple Linear Regression Test and Hypothesis Testing (t Test). Results: 1) Work Discipline has a positive and significant effect on Employee Performance with a t-statistic value of 2.610 and a probability value of 0.000 < α =0.05, 2) Work Motivation has a positive and significant effect on Employee Performance with a t-statistic value of 12,477 and a probability value of 0.000 < α = 0.05, 3) The work environment has a positive and significant effect on employee performance with a t statistic of 14,722 and a probability value of 0.000 < α = 0.05. These results can be obtained from the following regression equation: Y = 1.607 + 0.166 + X1 + 0.282 X2 + 0.505 X3.